(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study will analyze the relationship between two variables: the independent variable, the number of bank accounts in Iraq, and the dependent variable, the volume of bank deposits. The research hypothesis assumes a direct relationship between these two variables. After collecting data on four Iraqi banks and their deposit volumes over a decade (2015–2025) and comparing the change in deposit volume with the number of bank accounts in Iraq, the hypothesis was not supported. An increase in the number of bank accounts in Iraq does not necessarily mean an increase in the amount of money held in them, because most of these accounts were opened recently to transfer public sector employee salaries, and in most cases, the funds are withdrawn only once. In addition, other bank accounts are subject to influences such as financial or health crises or even negative rumors, which lead depositors to withdraw their money and hoard it or convert it into foreign currencies or precious metals.